Prospects and problems of medical tourism in Bangladesh - Mamun, Muhammad Z.; Andaleeb, Syed Saad (© 2013 Baywood Publishing Co., Inc., 2016)
This article was published in the International Journal of Health Services [©2013 Published by Baywood Publishing Co., Inc.] and the definite version is available at: http://doi.org/10.2190/HS.43.1.i The Article's website is at: http://joh.sagepub.com/content/43/1/123